The GOGREEN survey: the environmental dependence of the star-forming galaxy main sequence at 1.0 < z < 1.5. Issue 4 (4th March 2020) - Old, Lyndsay J; Balogh, Michael L; van der Burg, Remco F J; Biviano, Andrea; Yee, Howard K C; Pintos-Castro, Irene; Webb, Kristi; Muzzin, Adam; Rudnick, Gregory; Vulcani, Benedetta; Poggianti, Bianca; Cooper, Michael; et al.
ABSTRACT: We present results on the environmental dependence of the star-forming galaxy main sequence in 11 galaxy cluster fields at 1.0 < z < 1.5 from the Gemini Observations of Galaxies in Rich Early Environments Survey (GOGREEN) survey. We use a homogeneously selected sample of field and cluster galaxies whose membership is derived from dynamical analysis. Using [OII ]-derived star formation rates (SFRs), we find that cluster galaxies have suppressed SFRs at fixed stellar mass in comparison to their field counterparts by a factor of 1.4 ± 0.1 (∼3.3σ) across the stellar mass range: 9.0 < log ( M * /M⊙ ) < 11.2. We also find that this modest suppression in the cluster galaxy star-forming main sequence is mass and redshift dependent: the difference between cluster and field increases towards lower stellar masses and lower redshift. When comparing the distribution of cluster and field galaxy SFRs to the star-forming main sequence, we find an overall shift towards lower SFRs in the cluster population, and note the absence of a tail of high SFR galaxies as seen in the field. Given this observed suppression in the cluster galaxy star-forming main sequence, we explore the implications for several scenarios such as formation time differences between cluster and field galaxies, and environmentally induced star formation quenching and associated time-scales.